Webcam-based distance and surface estimation system for microwave imaging - Felício, J. M. (2019)
One of the critical steps in Medical Microwave Imaging (MMWI) algorithms is the calculation of the distances between the antenna and the synthetical focal point, due to the different propagation velocities in the tissues and background medium. In fact, it has a major influence on the image accuracy. As a result, it is very important to have a priori information about the shape of the body part under examination. Here we propose a low cost optical system based on a single commercial webcam. We validate the new system by showing an application to breast imaging, where we reconstruct the scatterers inside the breast using the real and estimated shapes. The results show very good resemblance, thus proving the new system supplies a reliable estimation of the breast shape.